Spin injection and helicity control of surface spin photocurrent in a three dimensional topological insulator - Y. Q. Huang (Nature Portfolio, 2017)
Surface spin current in a 3D topological insulator (TI) remains difficult to control and the out-of-plane spin texture is largely unexplored. Here, the authors identify subtle effect of the spin texture on surface photocurrent and demonstrate controlled spin injection from a semiconductor to a TI.